PENGARUH APLIKASI BIOCHAR SEKAM PADI DAN KOMPOS TERHADAP SIFAT KIMIA TANAH, PERTUMBUHAN, DAN SERAPAN FOSFOR TANAMAN JAGUNG PADA ULTISOL - Diva Ariella Herhandini; Retno Suntari; Ania Citraresmini (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
Rice husk biochar and compost application are expected to improve soil chemical properties such as pH, organic carbon, and available P in Ultisol, which in turn improves crop growth and P uptake by plants. The purpose of this research was to analyze the effect of the combination of rice husk biochar and compost on the soil chemical properties (pH, organic carbon, and available P), maize growth, and P uptake by maize in an Ultisol. The research used a Randomized Block Design with six treatments (P0: control; P1: 4 t biochar ha-1; P2: 30 t compost ha-1; P3: 4 t biochar ha-1 and 30 t compost ha-1; P4: 8 t biochar ha-1 and 30 t compost ha-1; P5: 4 t biochar ha-1 and 60 t compost ha-1) and four replications. The result showed that the combination of 8 t rice husk biochar ha-1 and 30 t compost ha-1 showed a significant effect on increasing pH, organic carbon, and available P in an Ultisol, increasing the height of maize crops at 4 and 6 WAP (weeks after planting). However, it had no effect on the number of leaves and showed an effect on the increase in P uptake of maize crop.